Musterhafter Rechtsstaat, czyli o narodowosocjalistycznej koncepcji państwa prawa (1933-1939) - Zygmunt, Maciej (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The article aims to analyse the National Socialist way of considering the rule of law concept in a comparative aspect with its essential elements in the traditional perspective. The author, following the representatives of the legal science, reconstructs the meaning of principles underpinning the rule of law and then relates them to the legal order of the Third Reich in the first stage of its functioning (1933-1939), political practice and the views of Nazi state law doctrine. Particular attention is given to the realisation of the principles of constitutionality, protection of fundamental rights (human dignity, individual freedom and equality before the law) and effective judicial protection.
Keywords: National Socialism; rule of law; racism; Rechtsstaat; Third Reich